Why life speeds up as you get older : how memory shapes our past - Draaisma, D. (Canto classics., 2012)
Why Life Speeds Up As You Get Older raises almost as many questions as it answers. Draaisma explores the nature of autobiographical memory, covering subjects such as dejvu, near death experiences and the effect of severe trauma on memory recall, as well as human perceptions of time at different stages in life.